Children's and adolescents' snacking: interplay between the individual and the school class - Giese, Helge; Taut, Diana; Ollila, Hanna; Baban, Adriana S.; Absetz, Pilvikki; Schupp, Harald T.; Renner, Britta (Frontiers in Psychology, 2015)
Objective: In schools, perceived norms of classmates facilitate but can also inhibit unhealthy food intake in children and adolescents. However, the role of actual class behaviors and attitudes is less established. Thus, the present study examined classmates’ actual eating behavior and food preferences in relation to actual food intake. In addition, it tested whether these normative effects are facilitated by corresponding individual and class food preferences or a positive social self-concept. Methods: The food preferences, social self-concept, and unhealthy snacking frequency of 734 Finnish, 829 German, and 555 Romanian children and adolescents (aged 8-19) from 127 school-classes were assessed. Results: Multilevel analysis at individual and class level showed that classmates shared similar snacking habits (14.7% variance). Moreover, the unhealthy food preference of a school-class was associated with its collective snacking (χ²(1) = 54.67, p < .001, PRV = .32). This effect was facilitated by individual, unhealthy food preferences (χ²(1) = 16.72, p < .001, PRV = .57) and a positive social self-concept (χ²(1) = 5.91, p = .015, PRV = .12). Conclusions: Actual class norms are related to children’s and adolescents’ eating, but their impact depends on individual differences in preferences and social self-concept.